How wave exposure, group size and habitat complexity influence foraging and population densities in fishes of the genus Halichoeres (Perciformes: Labridae) on tropical rocky shores - Nunes, José de Anchieta C. C.; Sampaio, Cláudio L. S.; Barros, Francisco (Marine biology, 2013)
Wave exposure and habitat complexity have been used to explain variations in the distribution patterns and behavior of many reef fishes. This study analyzed the influence of both factors on density and foraging activity, and the influence of group size on foraging in three species of the genus Halichoeres (Labridae) on tropical rocky shores. It was shown that initial phases (IP) and terminal phases (TP) Halichoeres , were influenced by wave exposure, although foraging in Halichoeres brasiliensis TP was not influenced by wave exposure. The IP in all three species were positively associated with rugosity and algal cover while the TP was positively associated with depth. Habitat complexity also influences foraging in these species. Group size influenced foraging activity, except in H. brasiliensis TP. We also found variations in microhabitat patches used for foraging between species and differences in the stomach contents between species and phases, showing that functional roles change in response to ontogenetic shifts.